The Effect Of Oil Palm Farming On Income Distribution And Poverty Alleviation in Swampland Area - Tuti Heiriyani; Luthfi Fatah (Universitas Lambung Mangkurat, 2011)
In Indonesia, almost a quarter of its area is swampland therefore swampland development is important. This research is purposed to understand whether or not the cultivation of oil palm in swampland area contribute to the improvement of farmer welfare, and to understand the effect of oil palm cultivation in swampland area on income distribution and poverty alleviation in the area. This research will combine two approaches: macro and micro levels. At macro level a Social Accounting Matrix (SAM) will be utilized to investigate the impacts of oil palm cultivation on income distribution. At micro level, analyses will focus on farmers, firm owners, and traders (brokers) of oil palm plantation. The research results reveal that the cultivation of oil palm in swampland area will benefit more the agriculture entrepreneur households and high level households both urban and rural. Oil palm commodity is important for labor income improvement and will benefit poor farmer households compared to other sectors or commodities in the economy. Policy implications are that support should be given to production side. The provision of input at reasonable and affordable price, extension, guidance, and research to support oil palm cultivation are some example of appropriate policy for development of oil palm. The government needs to support farmer to be an entrepreneur. This can be triggered through training and farmer capacity building, following by adequate support of rural micro finance that suitable and has strong commitment to support farmer initiating and running their business in oil palm industry.